(untitled) (Annals of Medical Research, 2021)
Aim: Contrast-induced acute kidney injury (AKI) may be seen after contrast agent exposure which is known as nephrotoxic. It is fact that, patients with AKI have an increased risk after contrast exposure compared to patients with normal renal function values. However, the incidence of contrast nephropathy after contrast exposure with AKI is not clear. In this study, we planned to investigate the incidence of contrast nephropathy in patients undergoing coronary angiography with AKI and whether there is an increased risk compared to the control group. Materials and Methods: The study was planned as a retrospective study and we investigated the clinical outcome of patients who underwent isoosmolar contrast angiography in the arterial phase with acute kidney injury between January 2014 and December 2017. Results: The number of AKI patients included in the study was 280 and the control group consisted of 478 participants. There was no statistically significant difference between two groups. (3.2% (n: 9) of patients with AKI contrast nephropathy vs 6.5% (n: 31) of patients with normal kidney function and contrast nephropathy) (p> 0.05). On the other hand, there was statistically significant difference between two groups according to diabetes mellitus (patients with contrast nephropathy 26 (65%) had diabetes vs 14 (35%) participants had no diabetes). This difference was statistically significant (p <0.05). Conclusion: In this study, in patients who underwent emergency angiography with a preliminary diagnosis of acute coronary syndrome in the emergency department, we did not find an increased risk of acute renal injury and contrast-enhanced nephropathy compared to the patient population with normal kidney function.